China National Assessment of Education Quality - Physical Education & Health (CNAEQ-PEH) 2015: An Introduction. Issue 2 (3rd April 2019) - Wu, Lili; Ma, Xiao; Shi, Yutong; Tao, Shasha; Yu, Yong; Wang, Sijia; Luo, Liang; Xin, Tao; Li, Youfa
ABSTRACT: Purpose : To summarize the framework and development procedure of the China National Assessment of Education Quality - Physical Education & Health in 2015 (CNAEQ-PEH 2015), an authoritative and evidence-based national surveillance protocol developed by the Ministry of Education of the People's Republic of China for Grade 4 and Grade 8 students.Methods : The framework of CNAEQ-PEH 2015 included a test battery of physical fitness and health outcomes and self-reported questionnaires regarding facilitators and barriers to physical fitness and health in school settings and family status, completed by students, teachers, and principals. A qualified, standardized, and responsible work procedure was generated to provide insights into the quality of data collection and supervision of large-scale school-based physical fitness testing implementation. Measure development, stratified unequal probability sampling, and implementation were included in the working procedure.Results : In the first circle of the CNAEQ-PEH conducted on June 18, 2015, 111, 173 Grade 4 students from 4, 015 elementary schools and 72, 243 Grade 8 students from 2, 461 middle schools, along with their principals ( n = 6, 447) and physical education (PE) teachers ( n = 11, 418), were sampled by probability proportionate to size (PPS) across 323 counties in China. Results provided detailed information regarding students' physical fitness outcomes, learning, lifestyle, and educational environment.Conclusions : CNAEQ-PEH 2015 is a large-scale assessment of physical fitness and health outcomes. It helps provide opportunities to understand the physical fitness and health status of Chinese Grade 4 and 8 students and to study the correlations of physical fitness and health, as well as their relationship with education-related indicators and academic performance.